Perbedaan Identitas Sosial antara Anggota Kelompok Reog Ponorogo dengan Anggota Kelompok Reog di luar Kota Ponorogo - Baharuddin, Fahyuni; Rachma, Eva Nur; Satrio, Prakrisno (Penerbit STKIP PGRI Bangkalan, 2020)
Indonesian original art is very diverse. One of them is Reog art which is an original art from the city of Ponorogo. The perpetrators of this traditional art then migrated throughout Indonesia by bringing the Reog art culture. Some cities that become their destinations include: Jember, Madiun, Ngawi, Yogyakarta, Palembang, South Sumatra, and Jakarta. Reog has the characteristics carried out communally, a combination of dance, sports, gamelan music and poetry. This study aims to see whether there are differences in social identity between members of the Reog Ponorogo group and members of the Reog group outside the city of Ponorogo. Social identity theory is related to a sense of connectedness, caring, proud; derived from one's knowledge in various categories of social membership with other members, even without the need to have a close personal relationship. (Hogg, 2006). Data is collected on a scale based on the concept of social identity from Ellemers (1999). The research subjects were 30 members of the Reog group in Ponorogo and 30 members of the Reog group outside the city of Ponorogo. Then the data collected was analyzed using the t test method. Statistical analysis showed that there were differences in social identity between members of the Reog Ponorogo group and members of the Reog group outside the city of Ponorogo.